RCOR1 promotes myoblast differentiation and muscle regeneration - Martina Pauk; Fan Wang; Petri Rummukainen; H. G. Mauricio Ramm; Hanna Taipaleenmäki; Riku Kiviranta (Cell Death Discovery)
Abstract RCOR proteins belong to a family of highly conserved transcription corepressors (RCOR1, RCOR2 and RCOR3) that regulate the activity of associated histone demethylase 1 (LSD1) and histone deacetylase 1/2 (HDAC 1/2) in chromatin-modifying complexes. Despite the described function of LSD1 in skeletal muscle differentiation and regeneration, the role of RCOR family in myogenesis remains unknown. We found that RCOR1 is highly expressed in proliferating myoblasts and activated satellite cells, but not in mature myofibers during postnatal skeletal muscle growth and regeneration. Silencing of RCOR1 impaired myoblast differentiation and fusion, as evidenced by reduced levels of myogenin and MyHC, key markers of myogenic commitment. Moreover, RCOR1 depletion impaired myoblast proliferation through upregulation of the cell cycle inhibitor P21. Although combined silencing of P21 and RCOR1 rescued the proliferation defect of RCOR1 deficiency alone, it failed to restore differentiation, suggesting that RCOR1 action on myoblast proliferation and differentiation is mediated via independent mechanisms. RCOR1 was found physically associated with LSD1 and myogenic regulatory factor MyoD and contributed to LSD1 stability in myoblasts via ubiquitination. Accordingly, the repressive effect of RCOR1 depletion on myogenic differentiation was rescued by LSD1 overexpression, indicating that RCOR1 exerts its function on myoblast differentiation primarily through LSD1. Consistently, in a mouse model of skeletal muscle injury, depletion of RCOR1, accompanied with reduction of LSD1, supressed satellite cell activation and differentiation which resulted in impaired muscle regeneration. Together, our findings indicate that RCOR1 acts in concert with LSD1 as a novel positive regulator of myogenesis and skeletal muscle regeneration.